Crystal plasticity finite element modelling of the extrusion texture of a magnesium alloy. (July 2015) - Shao, Yichuan; Tang, Tao; Li, Dayong; Tang, Weiqin; Peng, Yinghong
Abstract In this paper, a crystal plasticity finite-element model (CPFEM) is developed to simulate the hot extrusion texture of the magnesium alloy AZ31. The crystal plasticity model is implemented in ABAQUS™ via user interface VUMAT subroutine. The elasto-plastic self-consistent (EPSC) model is used as the basic polycrystal framework to simulate the slip and twinning during the extrusion. Furthermore, this framework is extended to account for the effects of the dynamically recrystallized (DRX) grains on the extrusion textures. Good agreement is found between the experimentally measured and simulated textures. The simulation results show that the presence of a secondary texture component around <?CDATA $\langle 11.0\rangle $ ?> <?MML 〈11.0〉 ?><inline-graphic xlink:href="ark:/27927/pgj14kd2f9j" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> || extrusion direction (ED) can be attributed to the lattice rotation around the c-axis during the formation of the DRX grains. In addition, the shear strain imposed on the extruded material affects the resulting texture by enhancing the basal <?CDATA $\langle a\rangle $ ?> <?MML 〈a〉 ?><inline-graphic xlink:href="ark:/27927/pgj14kd2g92" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> slip mode as the material passes through the extrusion opening.